Performance evaluation of modified asphalt mix with blister PVC waste - Cajina Cruz, Nicole (2025)
The modification of asphalt mix with waste polymers provides several benefits. Among the most important is the optimization of the performance of the mix and the increase in its useful life. Not to mention a reduction in the amount of plastic waste that does not have an adequate waste management. This article shows the results obtained from a study where a blister type waste material (composed of polymers such as PVC) was incorporated into an asphalt mixture by the dry method. Method in which, prior to the asphalt adhesion, the modifier is incorporated to the mix in substitution of part of the fine aggregate. The purpose of the study was to evaluate the performance of the mix and compare its mechanical behavior with a conventional mix. For the project development, the modifier was characterized, and the appropriate percentage was selected so that the design of the modified mixture would comply with Superpave requirements. With the optimized design, the test specimens were prepared, and their performance was evaluated based on the following tests: four-point beam bending, Hamburg wheel, retained tensile strength (moisture damage) and dynamic modulus. Since an adequate behavior of the modified mix was observed, its sensitivity was evaluated in a pavement structure; identifying in which layers of the asphalt mix should the material be used.